(untitled) (International Seven Journal of Multidisciplinary, 2024)
This article aims to present the conceptions of children between four and five years of age, regularly enrolled in Early Childhood Education, the first stage of Basic Education, about the elderly and human aging. In this sense, a bibliographic and field research was carried out. For data collection, Children’s Literature books were used, which explored the theme in a playful and accessible way for the age of the students, so that it was possible to collect children’s reports about their conceptions about human aging. Afterwards, the collected material was analyzed in the light of the bibliographic reference pertinent to the theme. According to what was analyzed, the results indicate that the theme of human aging is distant from the school environment and therefore appears in a superficial way within school contents, contributing to children presenting conceptions loaded with stereotypes about the elderly. It was also possible to observe that the children present different conceptions of the terms "elderly and old", which drew a lot of attention during data collection. The word "old" appeared in a pejorative way, while "elderly" children saw as people capable of performing activities. It is important to develop school curricula that work adequately with the theme of human aging from Early Childhood Education, as school is an intergenerational environment. Finally, it is through contact with the theme that the child may have different conceptions about the elderly and human aging.